2010
DOI: 10.1002/jqs.1313
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term vegetation history of the Mojave–Colorado desert ecotone at Joshua Tree National Park

Abstract: Thirty-eight dated packrat middens were collected from upper desert (930-1357 m) elevations within Joshua Tree National Park near the ecotone between the Mojave Desert and Colorado Desert, providing a 30 ka record of vegetation change with remarkably even coverage for the last 15 ka. This record indicates that vegetation was relatively stable, which may reflect the lack of invasion by extralocal species during the late glacial and the early establishment and persistence of many desert scrub elements. Many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 53 publications
(55 reference statements)
4
36
0
1
Order By: Relevance
“…yr bp . Although this suite of species is smaller than those from other regional midden series (Van Devender, ; Holmgren et al ., , ), these mostly summer‐flowering species nevertheless provide evidence for warm season precipitation during the late glacial and early Holocene.…”
Section: Resultsmentioning
confidence: 94%
“…yr bp . Although this suite of species is smaller than those from other regional midden series (Van Devender, ; Holmgren et al ., , ), these mostly summer‐flowering species nevertheless provide evidence for warm season precipitation during the late glacial and early Holocene.…”
Section: Resultsmentioning
confidence: 94%
“…Evidence from paleo-biological records indicates that Joshua trees, among many species, have shifted their distribution since the Pleistocene, when they were more broadly distributed in the southwestern United States (Smith et al 2011). While the ecotone between these deserts has shifted during glacial and inter-glacial cycles, as a whole, it is believed to have been quite stable since the end of the Pleistocene (Holmgren et al 2010). While the ecotone between these deserts has shifted during glacial and inter-glacial cycles, as a whole, it is believed to have been quite stable since the end of the Pleistocene (Holmgren et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Today, Joshua trees occur in a jagged continuous band across the western Mojave Desert and in fragmented populations to the north and east (Cole et al 2011); the occurrence of Joshua trees within JTNP defines the current southern extent of the Mojave Desert before it transitions into the Colorado Desert within the park. While the ecotone between these deserts has shifted during glacial and inter-glacial cycles, as a whole, it is believed to have been quite stable since the end of the Pleistocene (Holmgren et al 2010). Perhaps because of their iconic and keystone status, Joshua trees have received considerable attention with respect to their sensitivity to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Although external morphology was not visibly different, our results demonstrated that microbial communities and indicator microorganisms showed greater resolution to identify geographical pattern/separation at the Mojave-Colorado desert ecotone than morphological identification. Similar procedures previously identified a boundary of Mojave desert and Colorado desert using vascular plant taxon composition and key species [53]. Employing a similar procedure, we identified major fungal and bacterial components that contributed significantly to biocrust microbial geographical patterning (ANOVA, p < 0.05).…”
Section: Geographical Pattern: Does Geographical Location Structure Bmentioning
confidence: 68%